An application of K-Nearest Neighbor interpolation on calibrating corrosion measurements collected by two non-destructive techniques - Hamed, Y. (Institute of Electrical and Electronics Engineers Inc., 2016)
Every measuring equipment or inspection tool is known to have its own accuracy, which may affect the reliability of its measurements. This affects Oil and Gas pipeline corrosion measurements, which may affect data reliability if not well interpreted. The inspection tolerance occurred in the measurements should be treated carefully for each equipment to prevented misinterpretation of the data which could lead to incorrect assessment. This paper presents a new application of K-Nearest Neighbor interpolation to calibrate corrosion measurements collected by Magnetic Flux Leakage intelligent pig (MFL-IP) with the readings of Ultrasonic Testing (UT) scan device. The final enhanced metrics will be used in the integrity assessment report of the pipeline to decide whether the pipeline is fit for service or needs certain maintenance. Â© 2015 IEEE.